Analyzing and identifying geopolitical masculinity Garmasêr Kurdish women in the 20th century using AHP and GIS - Karim, Zeynab (Sulaimani Journal for Humanities, 2026)
The effect of the ambiguous and disputed geographical position of Garmasêr has been evident in human phenomena throughout history. Although geographical determinism has created many challenges for the Garmasêr women, they always seek empowerment. Based on the geopolitical position of Garmasêr, located in Iran, Iraq, and Kurdistan, two questions form the basis of this study. First, what were the characteristics of a Garmasêr woman in the 20th century? What criteria and factors have empowered the Garmasêr women? In this study, mixed methods of qualitative and quantitative were used. Based on the field method, 24 men and women between 40-60 years of age and experts in the semantic paradox of Masculinity in Kurdistan were randomly selected. Due to the geographical dispersion and high age of some interviewees, some data were collected via virtual interviews. In summary, Regarding the collected natural and human criteria through interviews and in-depth observations, AHP was used to evaluate them. Simultaneously, the Garmasêr domain based on the geopolitical masculinity criteria affecting women has been determined using GIS. Respectively, each of the selected criteria, after pairwise comparison, was valued; among the chosen criteria, Social was given the highest coefficients of importance. And among the selected sub-criteria, the Locating between borders achieved the most excellent coefficient of importance
Keywords: Geopolitical Masculinity; Garmasêr; AHP; GIS